1973
DOI: 10.1002/bip.1973.360120513
|View full text |Cite
|
Sign up to set email alerts
|

Conformational studies of anthrax polypeptide, subtilis polypeptide, and synthetic poly‐γ‐Lglutamic acid

Abstract: SynopsisPoly-y-L-glutamic acid has been synthesized by the activated pentachlorophenyl ester polymerization method and the molecule weight of the polymer was found to be 16,000. Comparative conformational studies on the synthetic and on the native polyglutamic acid obtained from B. anthracis and B. subtilis were carried out using optical rotatory dispersion, circular dichroism, peptide absorption spectrum, and titration data. These results show that poly-y-glutamic acid does not exhibit any conformational orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
5
7
0
Order By: Relevance
“…The relationship of the root mean square radius to the hydrodynamic radius in each case also suggests that the molecules are present in a random coil configuration. This finding is consistent with our CD analysis as well as with various literature reports of polyglutamic acids at neutral pH (36,37).…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…The relationship of the root mean square radius to the hydrodynamic radius in each case also suggests that the molecules are present in a random coil configuration. This finding is consistent with our CD analysis as well as with various literature reports of polyglutamic acids at neutral pH (36,37).…”
Section: Resultssupporting
confidence: 94%
“…The chemical identity and homogeneity of the PGGA preparation were confirmed by NMR and amino acid analysis, and the unambiguous structural determination verified the ␥-carboxyl isopeptide linkage. In agreement with previous reports (13,36), GC-FID analysis showed that Ͼ99% of the polymer was composed of D-glutamic acid. This isomeric homogeneity appears to be a unique characteristic of B. anthracis and has further implications for vaccine antigen development in that others have proposed use of polyglutamic acids derived from bacilli including Bacillus subtilis and Bacillus lichenformis, despite the fact that their capsules are often a mixture of D-and L-isomers (28,36).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations